2004
DOI: 10.1016/j.femsec.2004.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Performances and microbial features of a granular activated carbon packed-bed biofilm reactor capable of an efficient anaerobic digestion of olive mill wastewaters

Abstract: Anaerobic digestion of olive mill wastewaters is generally performed in anaerobic contact bioreactors where the removal of toxic phenols is often unsatisfactory. In the present work we show that a granular activated carbon packed-bed biofilm reactor can be successfully used to achieve effective and reproducible wastewater decontamination even at high organic loads. A comparison of 16S rRNA gene sequences of the inoculum and of biomass samples from different districts of the reactor revealed enrichment of speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 37 publications
3
34
1
1
Order By: Relevance
“…The process performances were comparable to those described by other authors. 5 In contrast to a recent study of a GAC biofilm reactor treating OMW, 5 where the only methanogen found was Methanobacterium formicicum, here Methanobacteriaceae and Methanosaeta/Methanothrix were the main methanogens in the reactor. These groups changed in relative abundance in response to increasing VOL.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…The process performances were comparable to those described by other authors. 5 In contrast to a recent study of a GAC biofilm reactor treating OMW, 5 where the only methanogen found was Methanobacterium formicicum, here Methanobacteriaceae and Methanosaeta/Methanothrix were the main methanogens in the reactor. These groups changed in relative abundance in response to increasing VOL.…”
Section: Discussioncontrasting
confidence: 57%
“…3,4 However, process efficiency can be seriously reduced owing to the presence of high concentrations (8-16 g L −1 ) of phenolic compounds. 5 During the degradation of complex organic matter by anaerobic digestion, methanogenic Archaea are the final catalysers of the food chain. By removing the metabolic products of syntrophic acetogens, methanogens play a regulative role in maintaining the overall efficiency of the process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Actinomyces suimastitidis and Staphylococcus felis were minor constituents of the biofilm formed [81]. Investigation of microbial dynamics in a granular activated carbon packed-bed anaerobic bioreactor fed with OMW resulted in the identification of members of Gammaproteobacteria , Deltaproteobacteria , and Bacteroidetes as well as fermentative bacteria of the genera Clostridium ( Firmicutes ) and Anaerobaculum ( Synergistetes ) [82]. Syntrophus spp., which were in syntrophic relationship with methanogenic Archaea , were detected, while sulphate-reducing bacteria were identified as the result of the high sulphate concentration in the OMW digested.…”
Section: Microbial Community Structure In Bioreactor Systems Treatmentioning
confidence: 99%
“…Therefore, the present study has additional significance in terms of expanding the usability of char materials. There have been previous studies in which activated carbon was used as the immobilization carrier in methane fermentation (Bertin et al, 2004), and, with respect to hydrogen production, activated carbon has been used as a core for granulation . However, few examples exist where woody waste chars are used in fermentative hydrogen production.…”
Section: Introductionmentioning
confidence: 99%